2004
DOI: 10.1021/ja048648p
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Well-Aligned Multiwalled Carbon Nanotubes in Confined Polyacrylonitrile Environments:  Electrospun Composite Nanofiber Sheets

Abstract: Highly oriented, large area continuous composite nanofiber sheets made from surface-oxidized multiwalled carbon nanotubes (MWNTs) and polyacrylonitrile (PAN) were successfully developed using electrospinning. The preferred orientation of surface-oxidized MWNTs along the fiber axis was determined with transmission electron microscopy and electron diffraction. The surface morphology and height profile of the composite nanofibers were also investigated using an atomic force microscope in tapping mode. For the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
246
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(260 citation statements)
references
References 34 publications
11
246
1
2
Order By: Relevance
“…This suggests that an increase in the SWCNT content enhances the thermal stability of the composite. Analogous behaviour has been reported in the literature for various polymer/CNT composites [34,35]. The observed stabilization may be attributed to the barrier effect of CNTs, which hinders the diffusion of the degradation products from the bulk of the polymer to the gas phase.…”
Section: Thermal Stabilitysupporting
confidence: 84%
“…This suggests that an increase in the SWCNT content enhances the thermal stability of the composite. Analogous behaviour has been reported in the literature for various polymer/CNT composites [34,35]. The observed stabilization may be attributed to the barrier effect of CNTs, which hinders the diffusion of the degradation products from the bulk of the polymer to the gas phase.…”
Section: Thermal Stabilitysupporting
confidence: 84%
“…The improved mechanical and electrical properties of above aligned nanotube/polymer composite have been realized through the direct use of nanotube arrays, sheets, and fibers. In the case of other approaches to align nanotubes (Baji et al, 2010;Ge et al, 2004;Go et al, www.intechopen.com 2004; Haggenmueller et al, 2003;Jang et al, 2009;Ji et al, 2009;Kang et al, 2009;Razal et al, 2007;Vigolo et al, 2000Vigolo et al, , 2002, similar improvements were also observed. For instance, aligned nanotube/polyacrylonitrile fibers after hot-stretching treatment showed a significant enhancement of tensile strength by 320.7% (Ji et al, 2009), while aligned nanotube/epoxy arrays induced by electric field could improve electrical conductivities by four orders of magnitude in the direction of alignment .…”
Section: Preparation Of Aligned Carbon Nanotube/polymer Compositessupporting
confidence: 60%
“…For instance, high-quality nanotube/polydiacetylene composite fibers were produced by the physical attachment of diacetylenic monomers followed by topochemical polymerization of diacetylenic moieties under UV light . Another widely explored method to aligned nanotube/polymer fibers is electrospinning, an electrostatically induced self-assembly process where nanoscale fibers were typically produced (Baji et al, 2010;Ge et al, 2004;Go et al, 2004;Kang et al, 2009). The surface tension, jet elongation, and slow relaxation of nanotubes contribute to orientation of nanotubes.…”
Section: Preparation Of Aligned Carbon Nanotube/polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies on controlling the spatial orientation of electrospun CNT/polymer composite nanofibres [109] [137] [138] [139] [140]. Modification of electrospinning setup has been a common approach to produce aligned electrospun composite nanofibres.…”
Section: A Carbon Nanotube Dispersionmentioning
confidence: 99%